RETHINKING CENTRE-PERIPHERY ASSUMPTIONS IN THE HISTORY OF EDUCATION Exchanges among Brazil, USA, and Europe. - Vidal, Diana Gonçalves, 1960-; Silva, Vivian Batista da. ([S.l.] : ROUTLEDGE, 2024)
This collection encompasses a period that spans two centuries, in which Brazil serves as a point of departure and of arrival for the analyses of circuits that, intertwined within the national borders, stimulate the reflection about international transits, hybridizations, and appropriations in a process of transnational circulation of subjects and artifacts, in which pedagogical and social models and knowledges are not excluded. The chapters deal with voyages, trajectories, and exchanges, rethinking the beliefs that for a long time drove politicians, educators, and scholars in search of the best ways to construct national systems of education. Firstly, because they presupposed the existence of fixed and univocal relationships that start from the supposed center toward the regions perceived as peripheral, with no margin for examining the reverse circuit. Secondly, they elided the perception of those territories as transitory and resulting from historically shifting geographic and symbolic constructions. Lastly, they ratified the violence of the processes of exclusion based on the attribution of subalternities brought about by a historiographic narrative in education that presents itself asa reference.
Keywords: Education -- Brazil; EDUCATION / General; EDUCATION / History